Comparative analysis of resistance to ALS-inhibiting herbicides in smallflower umbrella sedge (Cyperus difformis) populations from direct-seeded and puddled-transplanted rice systems. Issue 2 (7th March 2022) - Huang, Mengge; Long, Di; Zhou, Fengyan; Li, Jingbo; Tang, Wenwei; Zeng, Dongqiang; Wang, Yanhui
Abstract: The transition from puddled-transplanted rice ( Oryza sativa L.) (PTR) to direct-seeded rice (DSR) is gaining popularity in central China. In contrast, the PTR system is the most common practice in southwest China. Weeds are a major problem in the paddy fields of the DSR systems, and herbicides are widely used for weed control. However, the increased frequency and rate of herbicide use leads to the rapid evolution of resistance. Smallflower umbrella sedge ( Cyperus difformis L.) is a troublesome weed species in rice fields of China and is usually controlled by the acetolactate synthase (ALS)-inhibiting herbicide bensulfuron-methyl. Here, we collected 32 C. difformis populations from DSR systems (Hunan Province) and PTR systems (Guangxi Province) and investigated their resistance to bensulfuron-methyl. Results revealed 80% (8 out of 10) populations from Hunan Province and 14% (3 out of 22) populations from Guangxi Province had evolved resistance to bensulfuron-methyl. Five populations from Hunan Province (HN-2, HN-3, HN-5, HN-9, HN-10) possessing the Trp-574-Leu mutation had high-level resistance (ranging from 169- to >1, 309-fold) based on GR50 ratios. The resistant populations from Guangxi Province had a lower level of resistance to bensulfuron-methyl due to a Pro-197-Ser mutation. The Asp-376-Glu mutation was only identified in the HN-4 population. In addition, the GX-3 population from the PTR systems was resistant to bensulfuron-methyl without ALS gene mutations, indicating non–target site resistance (NTSR). Although some resistant populations of both regions exhibited cross-resistance to multiple ALS-inhibiting herbicides, including pyrazosulfuron-ethyl, bispyribac-sodium, penoxsulam, and imazapic, sensitivity was also detected to the auxin herbicide MCPA and the photosystem II–inhibiting herbicides bentazone and propanil. These results indicate that cultivation practices affect resistance evolution in C. difformis . DSR systems exert high selection pressure by selecting the Trp-574-Leu mutation, resulting in high-level resistance. In contrast, a mutation at Pro-197 plus NTSR likely plays a significant role in ALS resistance in the PTR systems.